Response of Broccoli (Brassica oleracia L.) to Different Irrigation Regimes (The Agriculturists, 2016)
The study was conducted at the experimental field of Horticulture Research Centre, BARI, Gazipur during Rabi seasons in three years (2012 to 2015) to investigate the response of broccoli (cv. Premium crop) under different irrigation regimes. The experiment was conducted in RCBD with five replications. There were four treatments: I1=Irrigation up to FC at 5 days interval after plant establishment (PE), I2= Irrigation up to FC at 10 days interval after PE, I3 = Irrigation up to FC at 15 days interval after PE and I4= Irrigation up to FC at 20 days interval after PE. A significant response of broccoli to different irrigation levels was observed. Among the different treatments, I2 (irrigation at 10 days interval) was significantly better yielding (19.98 t/ha, 20.63 t/ha and 16.24 t/ha in 1st, 2nd and 3rd year, respectively). The lowest yields were observed from the treatment I4 each in all 3 years. The highest seasonal water (382.30 mm, 296.58 mm and 305.00 mm in 1st, 2nd  and 3rd year) were used in treatment I1 and the lowest (204.60 mm, 185.66 mm and 179.77mm in the 1st, 2nd  and 3rd year) were used in treatment I4, I3 and I3, respectively. The results suggest that irrigation at 10 days interval (I2) might be optimum irrigation schedule for broccoli production on the basis of gross return. But in respect of economic profitability, the highest marginal rate of return is obtained from treatment I3.The Agriculturists 2016; 14(1) 98-106